Aktivitas Public Relations dalam Mengoptimalkan Keterlibatan Relawan (Volunteer Engagement) - Putri Vania Iftatunnisa; Istisari Bulan Lageni (STIKes Ibnu Sina Ajibarang, 2025)
Ocean Young Guards, an organization that focuses on marine conservation, faces communication challenges in implementing the Blue Carbon Journey campaign program, such as differences in expectations from volunteers and the barriers of marine languages ​​​​that become organizational barriers. The importance of transparent and proactive communication is in line with Ocean Young Guards' efforts to address climate change by involving the younger generation who can help run the Blue Carbon Journey campaign program to achieve marine conservation goals. This study aims to determine the involvement of the younger generation as volunteers in the Blue Carbon Journey campaign program implemented by Ocean Young Guards. This study uses a qualitative approach with a descriptive study method and the theories used in this study are Engagement Theory and Social Change Theory. Data collection techniques used in this study were interviews and documentation, the results of the study showed that volunteer involvement is very important for the success of campaign activities with the interaction of organizations and volunteers including transparency of information about the program, education about climate change that is happening and active involvement of volunteers in Blue Carbon Journey campaign activities. The success of the Blue Carbon Journey campaign contributed to increasing volunteer awareness of the importance of coastal and marine ecosystems as a solution to climate change, and motivated them to become agents of change in environmental conservation.